(untitled) (International Journal of Medical and Surgical Sciences, 2015)
In implantology, an increase in the bone thickness of the alveolar ridge is often associated with the use of autogenous bone, which is considered to be the gold standard. The aim of the present study was to report the clinical case of a patient with abnormal bone thickness in the alveolar ridge, causing severe esthetical damage, and the use of xenogeneic block bone grafts. A female, 43-year old patient exhibited a considerable bone defect in the region of teeth 11 (absent), although there was sufficient native bone available for the implantation. The patients treatment involved positioning the implant and performing a block bone graft using bone of bovine origin. The post-operative period passed without complications. The post-operative clinical examination confirmed the correction of the pre-existing esthetic defect and the health of the soft tissues involved. The tomographic examination 180 days post-surgery also confirmed an excellent increase in thickness. The bovine block bone graft used in the present case was shown to be viable in terms of correcting esthetic defects when there is sufficient native bone available for the implantation.